A maternally transmitted lethal neonatal progeroid syndrome with prominent genitourinary and gastrointestinal features. Issue 6 (June 1997) - Delatycki, M B; Cleary, M A; Bankier, A; McDougall, P N; Ahluwalia, J S; Chow, C W; Cooke-Yarborough, C M
Abstract : Twin brothers and their maternal uncle with a previously undescribed neonatal progeroid syndrome are presented. In addition to progeroid features, they had pseudo-obstruction of the urinary and gastrointestinal tracts, severe leucocytosis, liver dysfunction, and low complex III and IV in muscle but not in liver. Previously described neonatal progeroid syndromes and syndromes featuring pseudo-obstruction are discussed. The two most likely aetiological mechanisms are an X linked single gene disorder or a mitochondrial disorder. The evidence for these possibilities is presented.